Nise's control systems engineering - Nise, Norman S. (John Wiley & Sons, 2017)
Nise's Control Systems Engineering takes a practical approach, presenting clear and complete explanations. Real world examples demonstrate the analysis and design process, while helpful skill assessment exercises, numerous in-chapter examples, review questions and problems reinforce key concepts. A new progressive problem, a solar energy parabolic trough collector, is featured at the end of each chapter. Hardware Interface Laboratory experiments have been added to certain chapters. These experiments use National Instrument's myDAQ to interface your computer to actual hardware to test control system principles in the real-world.